The impact of consumer health information provided by libraries: the Delaware experience. - Pifalo, V (1997)
In the past two decades, consumer health libraries have proliferated in response to the changing health care environment and consumer demand. While this growth of consumer health resources and services has been extensively described in the literature, there is little documentation about the impact and value of providing consumer health information. This paper explores the issues of impact and value as examined in a retrospective study of consumers who received health information from the Delaware Academy of Medicine's Consumer Health Library during 1995. In this study, 270 adults were mailed a questionnaire that focused on whether the information influenced decisions, actions, anxiety levels, and patient-provider communication. The questionnaire also addressed the value of such library service in terms of likelihood of repeat use, recommendation to others, and willingness to pay. The results, based on a return rate of 86.7%, identified effects of library-supplied consumer health information that extend beyond the anticipated acquisition of knowledge to specific actions and effects on anxiety. The value of consumer health library information service was shown by the extremely high percentage of probable repeat use and recommendation to others, the willingness of 83.8% of the respondents to pay for such service, and the copious comments volunteered by the respondents.